HUBUNGAN POLA ASUH ORANG TUA DENGAN PERKEMBANGAN PADA ANAK USIA DINI ( 3-4 TAHUN) DI PAUD DHARMA WANITA DESA POJOKSARI KECAMATAN SUKOMORO KABUPATEN MAGETAN - Wulandari, Catur (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2016)
Guidance are sprouting children comprehensively and quality needs to be improved. Thisresearch purposes to analysis corolation between taking care system of parents with thegrowth on the early age children (3-4 years) in PAUD Dharma Wanita, Pojoksari villageSukomoro District Magetan Regency. The kind of research is obsevasional analitical withcross sectional researc desigh.The population is all of parent have children 3-4 years oldin PAUD Dharma Wnita, Pojoksari village are 30 parents,the great of samples use thetotal of population. The independent variable is parents’s taking care,while dependentvariable is the growth on the early age children (3-4 year ).The instrument to measuretaking care system is questioner with answer “ Never “ “Seldom” “Often” and growthuses KPSP.The data is analysed by univariate analysis with frequency distribution andbivariat analysis with chi square experiment with significant grade α ≤ 0,05. The resultsof research in get there is a relationship pattern foster parents with the development ofearly childhood (3-4 year). get mark ρ value 0,031 < α 0,05 with (r) 0,433 shows thatpower correlation being and direction of a positive relationship which means parallel.The conclusion of the research there is coralation between taking care system of parentsystem with the growt on the early age children in PAUD Dharma Wnita, Pojoksarivillage. Be suggested to Insthitution of healt service and Education service to giveillumination and socialiszation to parent have early age children about taking caresystem.